A Study on Prediction of Diabetic Coronary Heart Disease Using Machine Learning Algorithms - Madhumalar, S.; Sivakumar, S. (Journal of ISMAC, 2022)
One of the most prevalent illnesses in today's fast-paced culture is coronary heart disease in people with diabetes. It is challenging to foresee the onset of diabetic heart disease, a chronic ailment that affects people all over the world. One common misconception about machine learning is that it is an inaccessible field of study reserved for nerdy academics. However, concerning accuracy to predict disease based on symptoms, many studies have turned to machine learning methods, and this study provides a comparative analysis of these methods appeared in published research articles. This paper takes a close look at the research into predicting diabetic coronary artery disease using machine learning techniques, as well as the many different combinations of learning algorithms that have been employed to do so.
Keywords: Diabetic coronary heart disease; machine learning